DIMENSI PENILAIAN DALAM PENDIDIKAN ALAM SEKITAR MERENTAS PENGAJARAN DAN PEMBELAJARAN PENDIDIKAN ISLAM: DIMENSION OF EVALUATION IN ENVIRONMENTAL EDUCATION ACROSS THE TEACHING AND LEARNING OF ISLAMIC EDUCATION - Rekan, Abd. Aziz; Tengku Kasim, Tengku Sarina Aini; Md Yusoff, Yusmini (Journal of Islamic Educational Research, 2016)
Every religion especially Islam promotes the practices of environment sustainability in daily life. Islam, in particular emphasizes on the principles and etiquette of preserving and conserving the environment. The teaching and learning process of Islamic education in school is amongst the main medium to deliver the integral values of Islamic teachings on environment. The question is, how far teachers could measure the values that are being instilled to the students from the teaching and learning process. Therefore, a qualitative study has been carried out to explore teachers’ dimension of evaluation in environmental education across the teaching and learning of Islamic education in eco-school context. This study involves six informants among Islamic education teachers. Three dimensions of teachers’ evaluation have been identified as preliminary findings through the semi-structured interview. The outcome of this study highlights the strategies and challenges faced by the teachers which could either benefit the learning process or might require improvisation to strengthen the teaching process.